PENGARUH PERMAINAN MEMANCING IKAN MAS KOKI UNTUK KEMAMPUAN MENGENAL HURUF ANAK DI TAMAN KANAK-KANAK AISYIYAH 14 PADANG - Fitriyanti, Anggi; Rakimahwati; Yulsyofriend; Anggraini, Vivi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of the goldfish fishing game on children's letter recognition ability at TK Aisyiyah 14 Padang. This research employed a quantitative approach with a quasi-experimental design, specifically a pretest-posttest control group design. The subjects were group A kindergarten children divided into experimental and control classes. Data were collected through observation and letter recognition tests, including identifying letter shapes, naming letters, and associating letters with sounds.The results showed a significant improvement in children's letter recognition ability after the implementation of the goldfish fishing game. This finding is supported by previous studies indicating that activity-based games such as alphabet fishing significantly improve children's letter recognition skills . Therefore, the goldfish fishing game can be used as an effective and enjoyable learning medium to enhance early literacy skills in early childhood education.